Cell culture and somatic cell genetics of plants - Vasil, I. K.; Constabel, F.; Schell, Jozef S. (Jozef Stephaan), 1935-2003; Bogorad, Lawrence, 1921-2003 (Academic Press, 1984)
V. 1. Laboratory procedures and their applications.--v. 2. Cell growth, nutrition, cytodifferentiation, and cryopreservation.--v. 3. Plant regeneration and genetic variability.--v. 4. Cell culture in phytochemistry.--v. 5. Phytoche micals in plant cell cultures.--v. 6. Molecular biology of plant nuclear genes. --v. 7A. The molecular biology of plastids.--v. 7B. The photosynthetic apparatus: molecular biology and operation.--v. 8. Scale-up and automation in plant propagation.